Sinking Diatom Assemblages as a Key Driver for Deep Carbon and Silicon Export in the Scotia Sea (Southern Ocean) - Zúñiga, D.; Sanchez-Vidal, A.; Flexas, M. M.; Carroll, D.; Rufino, M. M.; Spreen, G.; Calafat, A.; Abrantes, F. (Frontiers in Earth Science, 2021)
Physical and biogeochemical processes occurring in the Southern Ocean are fundamental for modulating the global climate. In this context, a process-based understanding of how Antarctic diatoms control primary production and carbon export, and hence global-ocean carbon sequestration, has been identified as a scientific priority. Here we use sediment trap observations in combination with a data-assimilative ocean biogeochemistry model (ECCO-Darwin) to understand how environmental conditions trigger diatom ecology in the iron-fertilized southern Scotia Sea. We unravel the role of diatoms assemblage in controlling the biogeochemistry of sinking material escaping from the euphotic zone, and discuss the link between changes in upper-ocean environmental conditions and the composition of settling material exported from the surface down to 1000 m depth from March 2012 to January 2013. The combined analysis of in situ observations and model output suggests that an anomalous sea-ice episode in early summer 2012-13 favored (via restratification due to sea-ice melt) an early massive bloom of Corethron pennatum that rapidly sank to deep waters. This event drove high biogenic silicon to organic carbon export ratios, while modulating the carbon and nitrogen isotopic signals of sinking organic matter reaching the deep ocean. Our findings highlight the role of diatom ecology in modulating silicon vs. carbon sequestration efficiency, a critical factor for determining the stoichiometric relationship of limiting nutrients in the Southern Ocean.